Heuristic recurrent algorithms for photonic Ising machines - Charles Roques-Carmes (Nature Portfolio, 2020)
Application-specific computational hardware helps to solve the limitations of conventional electronics in solving difficult calculation problems. Here the authors present a general heuristic algorithm to solve NP-Hard Ising problems in a photonics implementation.